Cooperative Learning Models and the Improvement of Mathematical Problem Solving Skills: Key Findings from a Meta-Analysis Study - Pratikta, Maulana Eka; Caswita, Caswita; Firdaus, Rangga (Universitas Islam Sultan Agung, 2025)
Abstract. This study aims to evaluate the extent to which cooperative learning models influence the improvement of students' mathematical problem-solving skills. This research employed a meta-analysis method by analyzing 22 primary studies published in nationally accredited journals between 2018 and 2024. The selected studies, obtained through Google Scholar, involved subjects from junior high schools, senior high schools, vocational schools, and higher education. Data were analyzed using the Comprehensive Meta-Analysis (CMA) software, following procedures such as calculating effect sizes, testing for heterogeneity, selecting an appropriate estimation model, and detecting publication bias. The analysis revealed an overall effect size of 1.242, which is categorized as strong. These findings indicate that implementing cooperative learning models significantly positively impacts students' mathematical problem-solving abilities.Keywords: Cooperative Learning, Mathematical Problem-solving, Meta-analysis